Circuit design techniques for a gigahertz integer microprocessor - Nowka, K.J.; Galambos, T. (Proceedings International Conference on Computer Design. VLSI in Computers and Processors (Cat. No.98CB36273), 1998)
Using highly optimized, custom circuits and fast dynamic array control structures, a small team of designers at the IBM Austin Research Laboratory has developed a one gigahertz microprocessor. This paper describes the custom datapath circuit technology employed in this design. Particular attention was paid in the design process to the trade-off between performance and noise-margins. To achieve the low circuit latencies, highly-optimized and noise-characterized delayed-reset domino circuits were employed in the datapath elements of the gigahertz design.